How does light regulate plant regeneration? - Han, Juan; Li, Yapeng; Zhao, Ye; Sun, Yuhan; Li, Yun; Peng, Zuodeng (Frontiers in Plant Science, 2025)
Based on the totipotency and pluripotency of cells, plants are endowed with strong regenerative abilities. Light is a critical environmental factor influencing plant growth and development, playing an important role in plant regeneration. In this article, we provide a detailed summary of recent advances in understanding the effects of light on plant regeneration, with a focus on the fundamental processes and mechanisms involved in de novo shoot regeneration, somatic embryogenesis, and adventitious root formation. We focus on summarizing the effects of light intensity, light spectra, and photoperiod on these regeneration processes. Additionally, we propose the molecular mechanisms and regulatory networks underlying light-mediated plant regeneration. This article aims to deepen our understanding of the role of light in plant regeneration and to pave the way for future research on light-regulated regenerative processes in plants.